Effective removal of the herbicide glyphosate by the kelp Saccharina japonica female gametophytes from saline waters and its mechanism elucidation. (July 2021) - Tang, Xianming; Shen, Linsong; Liu, Shangshu; Gao, Jiangtao
Abstract: Glyphosate has been widely and extensively used for weed control because of its excellent herbicidal profile and low costs. However, more than 750 glyphosate products are on the market and are increasingly regarded as water pollutants as they cause adverse effects on aquatic life. Dry cell weight and photosynthesis of Saccharina japonica female gametophytes increased when glyphosate was used as the sole phosphorus source at the concentration of less than 20 mg L −1 . Nuclear magnetic resonance (NMR) analysis unambiguously confirmed that female gametophytes of the brown alga Saccharina japonica have the capability of breaking the C–P bond of glyphosate to orthophosphate, which finds the enormous potential of the most common seaweed to degrade the most widely used herbicide in the world. Furthermore, this is the first report on the use of glyphosate as the sole phosphorus source for the growth of eukaryotic cells. Because of the wide distribution and relatively easy cultivation of the fast-growing brown alga Saccharina japonica on the coast, our results set a promising stage for developing large macroalgae-based biotechnologies that can be applied for the remediation of contaminated seawater, which is greener and more cost-effective than conventional treatment methods. Highlights: Female gametophytes of the brown alga Saccharina japonica can utilize glyphosate at low concentration of glyphosate. The herbicide glyphosate inhibits the growth of female gametophytes at high concentrations. The brown alga Saccharina japonica can be a good alternative to seawater bioremediation to remove glyphosate.